Reform of the CMDI framework: Driving off with the breaks on - Ioannis G. Asimakopoulos; Tobias Tröger (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2024)
The lack of a European Deposit Insurance Scheme (EDIS) - often referred to as the "third pillar" of Banking Union - has been criticized since the inception of the EU Banking Union. The Crisis Management and Deposit Insurance (CMDI) framework needs to rely heavily on banks' internal loss absorbing capacity and provides little flexibility in terms of industry resolution funding. This design has, among others, led to the rare application of the CMDI, particularly in the case of small and medium sized retail banks. This reluctance of resolution authorities weakens any positive impact the CMDI may have on market discipline and ultimately financial stability. After several national governments pushed back against the establishment of an EDIS, the Commission recently took a different approach and tried to reform the CMDI comprehensively, without seeking to erect a "third pillar". The overarching rationale of the CMDI Proposal is to make resolution funding more flexible. To this end, the proposal seeks to facilitate contributions from (national) deposit guarantee schemes (DGS). At the same time, the CMDI Proposal tries to broaden the scope of resolution to include smaller and medium sized banks. This paper provides an assessment of the CMDI Proposal. It argues that the CMDI Proposal is a step in the right direction but cannot overcome fundamental deficiencies in the design of the Banking Union.
Keywords: G01; G18; G21; G28; K22; K23; 330; bank resolution; CMDI; EDIS; bail-in; transfer strategies; MREL; Banking Union